Effectiveness of mHealth interventions to promote physical activity and reduce sedentary behaviours on work-related productivity and performance: a systematic review protocol - Kyoko Nomura; Takako Miki; Michiko Nohara (BMJ Open)
Introduction Technologies such as health and fitness applications (apps) and wearable activity trackers have recently gained popularity and may play a key role in promoting physical activity and reducing sedentary behaviours. Although several systematic reviews have investigated their efficacy in physical activity and sedentary behaviours, few studies have focused on their impact on work-related outcomes among workers. Here, to explore the effects of mHealth interventions designed to encourage physical activity and decrease sedentary behaviours on work-related outcomes, including absenteeism, presenteeism, productivity, work performance and workability among workers, we will conduct a systematic review based on recent articles and an extensive literature search.Methods and analysis The literature search will be performed using PubMed, Web of Science, the Cochrane Library and the Japan Medical Abstracts Society from inception to 23 September 2023. We will select studies that (1) investigated the impact of mHealth interventions to promote physical activity and reduce sedentary behaviours on work-related outcomes such as absenteeism, presenteeism, productivity, work performance and workability; (2) were designed as a randomised controlled trial (RCT) or non-randomised study of interventions (NRSI); (3) were conducted among workers and (4) were published as full-text original articles in Japanese or English. We will assess the review quality with the AMSTAR 2 tool. The risk of bias will be assessed with the RoB tool 2.0 and ROBINS-I.Ethics and dissemination Ethical approval is unnecessary as the study will rely solely on previously published articles. The research results will be submitted for publication in a peer-reviewed scientific journal.Trial registration number The study protocol has been registered with the UMIN Clinical Trials Registry (ID=UMIN000052290).